Therapy for cutaneous T-cell lymphoma using low-dose bexarotene combined with phototherapy or alpha-interferon: Report of eight cases treated in Hospital Nacional Edgardo Rebagliati-Martins, Lima, Peru between 2003 and 2007 - Beltrán Gárate, Brady (2018)
Introduction: Bexarotene is a rexinoid compound that is approved for use in the therapy for early and advanced stage cutaneous T-cell lymphoma (CTCL).Clinical Cases: We present in this report the results of the use of low-dose bexarotene plus phototherapy or alpha-interferon, nine million units, in the treatment of CTCL. Eight patients were treated, five had mycosis fungoides, two had CD-8 epidermothropic aggressive lymphoma. The overall response rate was 62.5% (5/8), and the mean duration of response was 20 months. Low-dose bexarotene combined with phototherapy or alpha-interferon may be effective in the treatment of CTCL.